Achieving Carbon Neutrality for A Future Large Greenhouse Gas Emitter in Quebec, Canada: A Case Study - Patrick Faubert; Sylvie Bouchard; Rémi Morin Chassé; Hélène Côté; Pierre-Luc Dessureault; Claude Villeneuve (Atmosphere, 2020)
To reach the Paris Agreement targets of holding the global temperature increase below 2 °C above the preindustrial levels, every human activity will need to be carbon neutral by 2050. Feasible means for industries to achieve carbon neutrality must be developed and assessed economically. Herein we present a case study on available solutions to achieve net-zero carbon from the get-go for a planned liquefied natural gas (LNG) plant in Quebec, which would classify as a large Canadian greenhouse gas (GHG) emitter. From a literature review, available options were prioritized with the promoter. Each prioritized potential solution is discussed in light of its feasibility and the associated economic opportunities and challenges. Although net-zero carbon is feasible from the get-go, results show that the promoter should identify opportunities to reduce as much as possible emissions at source, cooperate with other industries for CO2 capture and utilization, replace natural gas from fossil sources by renewable sources and offset the remaining emissions by planting trees and/or buying offsets on the compliance and voluntary markets. As some of these solutions are still to be developed, to ensure timely net-zero pledge for the lifespan of the LNG plant, a portfolio and progressive approach to combine offsets and other options is preferable.